Artificial sweeteners and their implications in diabetes: a review - Angelin, Matcha; Kumar, Janardhanan; Vajravelu, Leela Kakithakara; Satheesan, Abhishek; Chaithanya, Venkata; Murugesan, Ria (Frontiers in Nutrition, 2024)
Diabetes is a significant global health concern, highlighting the critical role of dietary strategies in its management and prevention. Artificial sweeteners (ASs), due to their capacity to provide sweetness without contributing to caloric intake, have emerged as a potential tool in diabetes management. This review thoroughly examines the nuanced relationship between artificial sweeteners and diabetes, addressing their benefits and potential risks. ASs have been shown to aid in weight management, a key factor in reducing diabetes risk, and do not impact immediate blood glucose levels, offering improved glucose control for individuals with diabetes. Beyond these benefits, however, artificial sweeteners may interact complexly with gut microbiota, potentially altering its composition and affecting metabolic health. This interaction introduces concerns regarding insulin sensitivity and the risk of insulin resistance, with studies reporting conflicting findings. This comprehensive review highlights the importance of a nuanced approach to understanding the implications of artificial sweeteners in diabetes management. Given the mixed evidence on their health effects, there is a clear need for further research to fully elucidate the role of artificial sweeteners in metabolic health and their suitability as part of dietary interventions for diabetes.